The Moral Economy of Incel Discourse: From a Subsistence Minimum to a Recognition Threshold in Attention Markets - G. Franco, Yanna; Molina García, Berta (Historia y Comunicación Social, 2026)
Drawing on the moral economy tradition, we propose the concept of the Incel Moral Economy (IME) as a set of norms and expectations about deservingness and obligations that shape the distribution of status and, consequently, access to affective–sexual relationships with women. We conduct a qualitative study based on the construction and analysis of a purposive corpus of entries from the collaborative encyclopedia The Incel Wiki. IME provides an explanatory framework for approaching incels’ lived grievances within a neoliberal context that frames intimate relations as a market, and within attention markets on social media. The reviewed literature shows that platforms amplify and monetize this lexicon and these economistic codes for interpreting and expressing human relationships, and documents gateway pathways toward far-right repertoires.
Keywords: incels; Moral Economy; Incel Moral Economy (IME); digital misogyny; manosphere